Cork derived laser-induced graphene for sustainable green electronics. (1st September 2022) - Silvestre, Sara L; Pinheiro, Tomás; Marques, Ana C; Deuermeier, Jonas; Coelho, João; Martins, Rodrigo; Pereira, Luís; Fortunato, Elvira
Abstract: The demand for smart, wearable devices has been dictating our daily life with the evolution of integrated miniaturized electronics. With technological innovations, comes the impactful human footprint left on the planet's ecosystems. Therefore, it is necessary to explore renewable materials and sustainable methodologies for industrial processes. Here, an eco-friendly approach to producing flexible electrodes based on a single-step direct laser writing is reported. A 1.06 µ m wavelength fiber laser was used for the first time to produce porous three-dimensional laser-induced graphene (LIG) on an agglomerated cork substrates. The obtained material exhibits the typical Raman spectra, along with an exceptionally low sheet resistance between 7.5 and 10 ohm sq −1 . LIG on cork high electrical conductivity and the friendliness of the used production method, makes it an interesting material for future technological applications. To show its applicability, the production of planar micro-supercapacitors was demonstrated, as a proof of concept. Electrochemical performance studies demonstrate that LIG interdigitated electrodes, using PVA-H2 SO4 electrolyte, achieve an area capacitance of 1.35 mF cm −2 (103.63 mF cm −3 ) at 5 mV s −1 and 1.43 mF cm −2 (109.62 mF cm −3 ) at 0.1 mA cm −2 . In addition, devices tested under bending conditions exhibit a capacitance of 2.20 mF cm −2 (169.22 mF cm −3 ) at 0.1 mA cm −2 . Here, showing that these electrodes can be implemented in energy storage devices, also successfully demonstrating LIG promising application on innovative, green, and self-sustaining platforms.